2020
DOI: 10.1002/ppul.25081
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemia in cystic fibrosis during an extended oral glucose tolerance test

Abstract: Background Hypoglycemia in cystic fibrosis (CF), in the absence of glucose‐lowering therapies, has long been identified as an important issue in the management of CF. There is currently still no unifying hypothesis for its etiology. Aim The aims of this study were to perform a 3‐h oral glucose tolerance test (OGTT) in participants with CF and (1) document glucose, insulin, glucagon, glucagon‐like‐peptide‐1 (GLP‐1), and glucose‐dependent insulinotropic peptide (GIP) release patterns within varying glucose toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 31 publications
2
12
0
Order By: Relevance
“…None of the patients with CFRD had hypoglycemia, while 79% (15/19) of the remaining subjects showed hypoglycemia at the 3-hour time point, with 5 being symptomatic (sweaty, clammy hands and dizzy). Similar to the study by Kilberg et al 24 , those with hypoglycemia had a higher peak glucose and delayed and higher insulin release 25 . Incretins, hormones produced by the intestines that signal insulin secretion after eating, were not different between groups, and there was no change in the counter regulatory glucagon response.…”
Section: Cystic Fibrosis Related Diabetessupporting
confidence: 82%
See 2 more Smart Citations
“…None of the patients with CFRD had hypoglycemia, while 79% (15/19) of the remaining subjects showed hypoglycemia at the 3-hour time point, with 5 being symptomatic (sweaty, clammy hands and dizzy). Similar to the study by Kilberg et al 24 , those with hypoglycemia had a higher peak glucose and delayed and higher insulin release 25 . Incretins, hormones produced by the intestines that signal insulin secretion after eating, were not different between groups, and there was no change in the counter regulatory glucagon response.…”
Section: Cystic Fibrosis Related Diabetessupporting
confidence: 82%
“…Another outcome of screening for CFRD, can be the appearance of post-prandial or OGTT-related hypoglycemia. While the mechanism remains unclear, it is speculated to be related to derangement in glucose homeostasis involving both insulin and glucagon 24,25 . Kilberg et al 24 used a mixed meal tolerance test (MMTT) in 34 nondiabetic adolescents and young adults with pancreatic insufficiency, finding 26% (9/34) with hypoglycemia.…”
Section: Cystic Fibrosis Related Diabetesmentioning
confidence: 99%
See 1 more Smart Citation
“… 29 Along the same lines, Kilberg et al 21 showed that reduced glucagon secretion hours after a meal can lead to hypoglycemic events in CF patients diagnosed with pancreatic insufficiency. The dysregulation of glucagon secretion, with impaired high secretion in the early post-prandial phase 20 , 24 followed by a failed counter-regulatory response in the later phase 20 , 30 is not well understood.…”
Section: Biochemical and Histopathological Features Of Cfrdmentioning
confidence: 99%
“… 26 Rather, the only established secretion abnormality is failed counter-regulatory secretion of glucagon in late phases of OGTT trials, even though there may be some aberrant increased secretion in the early phase. 20 , 21 , 30 …”
Section: Evidence For Endocrine Pancreatic Dysfunction Leading To Cfrdmentioning
confidence: 99%